2007
DOI: 10.1111/j.0030-1299.2007.15289.x
|View full text |Cite
|
Sign up to set email alerts
|

Stream mosses as chemically‐defended refugia for freshwater macroinvertebrates

Abstract: Marine and terrestrial studies show that small, sedentary herbivores that utilize plants as both food and habitat can gain enemy-free space by living on hosts that are chemically defended from larger, generalist consumers. Although large herbivores are increasingly recognized as important consumers of macrophytes in freshwater communities, the potential indirect effects of herbivory on plant-associated macroinvertebrates have rarely been studied. Here, we show that the large, generalist consumers in a riverine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 75 publications
3
14
0
Order By: Relevance
“…This study offers strong evidence that mosses are chemically defended against generalist herbivores, corroborating other studies (Davidson et al., 1989, 1990; Parker et al., 2007), and suggesting mosses should be given much more attention in the field of plant–insect interactions. Secondary chemicals of mosses have been largely ignored by chemical ecologists and agricultural entomologists, but they might offer novel pathways of defense that have proved effective over evolutionary timescales.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study offers strong evidence that mosses are chemically defended against generalist herbivores, corroborating other studies (Davidson et al., 1989, 1990; Parker et al., 2007), and suggesting mosses should be given much more attention in the field of plant–insect interactions. Secondary chemicals of mosses have been largely ignored by chemical ecologists and agricultural entomologists, but they might offer novel pathways of defense that have proved effective over evolutionary timescales.…”
Section: Discussionsupporting
confidence: 89%
“…Most previous work on chemical defenses of bryophytes has implicated phenolic compounds, which tend to be soluble in water (Davidson et al., 1989; Liao, 1993; Glime, 2006). However, Parker et al. (2007) thoroughly explored the bioactivity of extracts of the aquatic moss F. novae‐angliae , and found that hexane‐ and chloroform‐soluble fractions were deterrent to stream herbivores, but water‐soluble fractions showed no activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many complex co-evolving biotic interactions [106][107][108]. We only tested here for the effect of green algae cover on vascular plants.…”
Section: Long Term Changes: Climate Management Practices and Biotic mentioning
confidence: 99%
“…The bryophytes associated with stones in low-order lotic environments accumulate particulate organic matter (Habdija et al, 2004) and are used as substrate for colonization of periphyton (Stream Bryophyte Group, 1999), providing food and shelter against the water current (Rosa et al, 2011(Rosa et al, , 2013Rodrigues et al, 2013) and refuge from predators (Glime and Clemons, 1972;Parker et al, 2007;Alvarez and Peckarsky, 2013) for various species of aquatic invertebrates. Several studies (Percival and Whitehead, 1929;Suren, 1993;Linhart et al, 2002;Tokeshi and Arakaki, 2012) have shown that these plants contribute to the dimensional complexity of the habitat within the stream flow, because they increase the surface area that can be colonized, resulting in a positive variation in the density and diversity of invertebrates.…”
Section: Introductionmentioning
confidence: 99%